Mood stability versus mood instability in bipolar disorder: a possible role for emotional mental imagery - Holmes, E; Deeprose, C; Fairburn, C; Wallace-Hadrill, S; Bonsall, M; Geddes, J; Goodwin, G (Elsevier, 2011)
A cognitive model of bipolar disorder suggests that mental imagery acts as an emotional amplifier of mood and may be heightened in bipolar disorder. First, we tested whether patients with bipolar disorder would score higher on mental imagery measures than a matched healthy control group. Second, we examined differences in imagery between patients divided into groups according to their level of mood stability. Mood ratings over approximately 6-months, made using a mobile phone messaging system, were used to divide patients into stable or unstable groups. Clinician decisions of mood stability were corroboarated with statistical analysis. Results showed (I) compared to healthy controls, patients with bipolar disorder had significantly higher scores for general mental imagery use, more vivid imagery of future events, higher levels of intrusive prospective imagery, and more extreme imagery-based interpretation bias; (II) compared to patients with stable mood, patients with unstable mood had higher levels of intrusive prospective imagery, and this correlated highly with their current levels of anxiety and depression. The findings were consistent with predictions. Further investigation of imagery in bipolar disorder appears warranted as it may highlight processes that contribute to mood instability with relevance for cognitive behaviour therapy.